2015
DOI: 10.1177/0284185114535209
|View full text |Cite
|
Sign up to set email alerts
|

Chest X-ray and CT findings of early H7N9 avian influenza cases

Abstract: Radiological changes associated with both acute pneumonia and acute interstitial inflammation were observed in early H7N9 avian influenza cases. Serial chest X-rays were useful for the diagnosis and severity assessment of the disease. CT may provide a more accurate assessment of the lung pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In other viral diseases that affects breathing, such as influenza or SARS, the damage produced to the lungs can be observed using pulmonary X-ray images. The works presented in Reference [11,12] detailed these effects in influenza, while other works like Reference [13,14] explain the effects in SARS patients.…”
Section: Introductionmentioning
confidence: 99%
“…In other viral diseases that affects breathing, such as influenza or SARS, the damage produced to the lungs can be observed using pulmonary X-ray images. The works presented in Reference [11,12] detailed these effects in influenza, while other works like Reference [13,14] explain the effects in SARS patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a study that involved 16 severe H7N9 infection cases, nine patients showed a low level of pleural effusion. Five suffered from moderate pleural effusion, four had mild seroperitoneum, and seven experienced mild pericardial effusion (7). In critical cases of influenza A virus subtype H1N1 (A/H1N1) infection, the imaging features include GGO, plaque-like shadows, massive consolidation of the lungs, pleural effusion, and pneumothorax (for patients who require mechanical ventilation) (8).…”
Section: Discussionmentioning
confidence: 99%
“…This difficulty may impair screening efficacy and work-up efforts. Chest X-rays (CXRs) are often considered as the first step in medical examinations of organs in the chest, as it's quickly and easily obtained besides lower dose of radiation exposure [12]. The presentation of PH in CXRs include enlargement of the central pulmonary arteries, with or without rapid tapering (pruning), and right heart chamber enlargement [13,14].…”
Section: Introductionmentioning
confidence: 99%